Beneficial Effects of the Genus Aloe on Wound Healing, Cell Proliferation, and Differentiation of Epidermal Keratinocytes - Moriyama, Mariko; Moriyama, Hiroyuki; Uda, Junki; Kubo, Hirokazu; Nakajima, Yuka; Goto, Arisa; Akaki, Junji; Yoshida, Ikuyo; Matsuoka, Nobuya; Hayakawa, Takao (PLOS ONE, 2016)
Aloe has been used as a folk medicine because it has several important therapeutic properties. These include wound and burn healing, and Aloe is now used in a variety of commercially available topical medications for wound healing and skin care. However, its effects on epidermal keratinocytes remain largely unclear. Our data indicated that both Aloe vera gel (AVG) and Cape aloe extract (CAE) significantly improved wound healing in human primary epidermal keratinocytes (HPEKs) and a human skin equivalent model. In addition, flow cytometry analysis revealed that cell surface expressions of β1-, α6-, β4-integrin, and E-cadherin increased in HPEKs treated with AVG and CAE. These increases may contribute to cell migration and wound healing. Treatment with Aloe also resulted in significant changes in cell-cycle progression and in increases in cell number. Aloe increased gene expression of differentiation markers in HPEKs, suggesting roles for AVG and CAE in the improvement of keratinocyte function. Furthermore, human skin epidermal equivalents developed from HPEKs with medium containing Aloe were thicker than control equivalents, indicating the effectiveness of Aloe on enhancing epidermal development. Based on these results, both AVG and CAE have benefits in wound healing and in treatment of rough skin.